Analisis Pengembangan Usaha Mie Balap di Jalan Tuasan yang Berawal dari Kegiatan Hobi Menuju Bisnis Berkelanjutan - Khairun Nisa; Shika Andari; Dhea Zuhrika (Universitas 45 Surabaya, 2024)
This research was conducted with the aim of analyzing how the racing noodle business developed from just a hobby to a sustainable business on Jalan Tuasan. With increasing public interest in practical food and distinctive flavors, the racing noodle business has become a popular choice and makes a positive contribution to the local economy. This research applies qualitative methods by collecting data through interviews and observations of business actors. From the research results, it was revealed that the main motivation behind this transformation was a love for cooking and a desire to share taste experiences with the community. However, business actors are also faced with challenges in the form of fierce competition and fluctuations in raw material prices. It is hoped that these findings can provide direction to prospective entrepreneurs and related parties in developing culinary businesses that are not only profitable but also sustainable, and support the growth of MSMEs in Indonesia.